Mystics and heretics in Italy at the end of the Middle Ages - Gebhart, Emile, 1839-1908, author.
1 online resource.
Keywords: Originally published in 1922, this translation of French historian mile Gebhart's work by Hulme gives a detailed religious history of Italy in the middle ages clearly demonstrating Gebhart's expertise in this area. Poetry, art and politics all centred around religion in the period studied and Gebhart identifies three key areas to be discussed; the Church in Rome, Christian concern and rationalism or secular independence whilst also focussing on famous heretics of the period including Arnold of Brescia and Francis of Assisi. This title will be of interest to students of History.